UPAYA PENINGKATAN KETERAMPILAN MEMBACA DENGAN PENGGUNAAN MEDIA KOMIK PADA KELAS III SEKOLAH DASAR - Alfiatus Sholehah; Moh Syamil; Mas’odi Mas’odi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Improving reading skills in grade 1 elementary school (SD) students is very important for building the basis of other learning skills. One effective method to achieve this goal is to utilize comic media. Comic media, which combines images and text, can attract students’ attention and make it easier for them to understand the stories they read. Using comics in learning to read can increase interest in reading, enrich vocabulary, and help students understand the story line more easily. Apart from that, comics can also stimulate students’ creativity through making simple comics. Therefore, using comic media in teaching reading in grade 1 elementary school can be a fun and effective strategy for improving students’ reading skills.